Tourism Potential and Strategy to Develop Competitive Rural Tourism in Indonesia - Dina Mayasari Soeswoyo; Mellia Jeneetica; Liliana Dewi; Made Handijaya Dewantara; Putu Swasti Asparini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This study aims to identify tourism potential and a set of strategies for a competitive rural tourism development using a case study in Sukajadi Tourism Village, Bogor Regency, West Java. This study is a descriptive qualitative type with an exploratory case study approach. Primary data were obtained from deep field observation and interview with key informants, while secondary data was obtained from the results of literature studies and documentation. This research used identification analysis techniques of 11 tourism components modified from several experts, CHSE analysis, work program government (PROKER), market preferences, and SWOT analysis as well as SWOT Matrix. The result of this study was obtained great potential and 15 main strategies for the development of the Sukajadi Tourism Village which is currently starting to grow, namely making serious and aggressive efforts on the internal aspects of village tourism destination, as well as collaboration with tourism industry and local governments to create a competitive rural tourism destination. An active and aggressive strategy is needed for the development of Sukajadi village as a competitive rural tourism destination, based on micro and macro perspectives.